Towards a universal approach for the finite departure problem in overlay networks - Koutsopoulos, Andreas; Scheideler, Christian; Strothmann, Thim Frederik (Inf. Comput.)

Algorithmic Foundations of Programmable Matter Dagstuhl Seminar 16271 - P. Fekete, Sandor; W. Richa, Andrea; Römer, Kay; Scheideler, Christian (SIGACT News)

Universal coating for programmable matter - Derakhshandeh, Zahra; Gmyr, Robert; W. Richa, Andrea; Scheideler, Christian; Strothmann, Thim Frederik (Theor. Comput. Sci.)

Improved Leader Election for Self-organizing Programmable Matter - J. Daymude, Joshua; Gmyr, Robert; W. Richa, Andrea; Scheideler, Christian; Strothmann, Thim Frederik (Algorithms for Sensor Systems - 13th International Symposium on Algorithms and Experiments for Wireless Sensor Networks, ALGOSENSORS 2017, Vienna, Austria, September 7-8, 2017, Revised Selected Papers)

Proceedings of the 29th ACM Symposium on Parallelism in Algorithms and Architectures, SPAA 2017, Washington DC, USA, July 24-26, 2017

Mechanische und mikrostrukturellen Eigenschaften additiv hergestellter Gitterstrukturen - Taube, A. (Hannover Messe Industrie, 2017, Hannover)

Entwicklung von Fahrradtretkurbelsystemen mittels additiver Fertigung - Brüggemann, J.P.; Risse, L.; Riemer, A.; Reschetnik, W.; Kullmer, G.; Richard, H.A. (Additive Fertigung von Bauteilen und Strukturen – Neue Erkenntnisse und Praxisbeispiele)

Methods for crack length measurement for the determination of fracture mechanical parameters of additive manufactured plastics - Bauer, B.; Reschetnik, W.; Kullmer, G.; Richard, H.A. (14th International Conference on Fracture)

Risslängenmessung in additiv gefertigten Kunststoffproben auf Basis von Steifigkeitsänderungen infolge Ermüdungswachstum. - Bauer, B.; Reschetnik, W.; Kullmer, G.; Richard, H.A. (DVM - Tagung - Additiv gefertigte Bauteile und Strukturen)

Bruchmechanische Charakterisierung von laserstrahlgeschmolzenen Werkstoffen - Reschetnik, W.; Brüggemann, J.P.; Kullmer, G.; Richard, H.A. (DVM - Tagung - Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Optimierung der Werkstoffeigenschaften von selektiv lasergeschmolzenen Aluminium 7075 - Brüggemann, J.P.; Reschetnik, W.; Aydinöz, M.E.; Richard, H.A.; Kullmer, G.; Hoyer, K.P.; Schaper, M. (DVM - Tagung - Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Strukturoptimierung von Kurzschaft-Hüftendoprothesen durch den Einsatz der additiven Fertigung - Risse, L.; Brüggemann, J.P.; Schramm, B.; Kullmer, G.; Richard, H.A. (DVM - Tagung - Zuverlässigkeit von Implataten und Biostrukturen)
improved sensorless control of PMSM are pointed out. The

Vergleich zweier Optimierungsstrategien am Beispiel additiv gefertigter Rennradvorbauten - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM Tagung - Additiv gefertigte Bauteile und Strukturen)

Konzepte zur Risslängenmessung an additive gefertigten Kunststoffen - Bauer, B.; Reschetnik, W.; Kullmer, G.; Richard, H.A. (DVM Tagung - Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen)

Entwicklung einer additiv gefertigten Fußorthese - Brüggemann, J.P.; Risse, L.; Schramm, B.; Richard, H.A. (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)

Crack length measurement of additive manufactured plastics based on the current potential drop method. - Bauer, B.; Reschetnik, W.; Kullmer, G.; Richard, H.A. (Symposium on Fatigue and Fracture of Additive Manufactured Materials and Components)

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, M.; Peters, K.; Taube, A.; Keller, A.; Hoyer, K.P.; Niendorf, T.; Grundmeier, G. (Materials and Corrosion)
FeMn-Ag alloys as potential bioresorbable implant materials were prepared by selective laser melting (SLM) from mixed powders of FeMn and Ag. The microstructure of the samples is characterized by presence of few micrometers to several tens of micrometer large Ag-phases within the FeMn matrix. The microstructure dependent corrosion and biomineralization processes in simulated body fluid (SBF) were studied in-situ by means of electrochemical impedance spectroscopy (EIS). The microstructure and local surface film formation were analyzed by electron microscopy (FE-SEM) and Raman microscopy. The results clearly show that the Ag-phase acts as a local cathode within the FeMn matrix. However, surface film formation is observed both for the Ag- and the FeMn-phases, which potentially lowers the self-corrosion as well as the galvanic coupling of the two phases. The formation of AgCl on the Ag-phases and mixed metal phosphates on the FeMn-phases can be observed by local Raman spectroscopic analysis in combination with FE-SEM characterization.

Experimental analysis and modeling of local ageing effects during laser sintering of polyamide 12 in regard to individual thermal histories - Josupeit, Stefan; Schmid, Hans-Joachim (Journal of Applied Polymer Science)
Polymer laser sintering (LS) is an important additive manufacturing (AM) technology. Individual and complex parts are directly produced from CAD data without the need of specific tools. The raw material is a polymer powder, which is deposited layerwise and melted selectively with a laser. Built parts are embedded in residual unmolten powder, the so-called part cake, which undergoes thermal ageing effects due to the exposure to high temperatures for long times during the manufacturing process. Hence, the recyclability of the unmolten powder is limited. This article focuses on a fundamental analysis of the ageing kinetics dependent on time, temperature, and oxygen content in the gas atmosphere. A model is developed and applied to measured, position-dependent process temperature histories to successfully predict the ageing distribution within a part cake. The results can be used to optimize the thermal process management in LS and to develop new efficient powder recycling methods.

BrOx cycle: A novel process for CO2-free energy production from natural gas - González Rebordinos, Jesús; Salten, Alexander Heinrich Johannes; Agar, David W. (International Journal of Hydrogen Energy)

Ein neuer Ansatz zur Beschreibung von Transportvorgängen in Füllkörperschüttungen - Salten, Alexander Heinrich Johannes; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

Warum ist unser Steuersystem so komplex? Eine befragungsbasierte Analyse - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)
Die Komplexität des Steuersystems stellt auch in Deutschland ein großes Problem dar. Entgegen bisherigen Betrachtungen weist die vorliegende Befragungsstudie darauf hin, dass die Treiber für steuerliche Komplexität deutlich vielfältiger und nicht nur im Gesetz, sondern auch in den steuerlichen Rahmenbedingungen zu verorten sind. Einerseits tragen übermäßig viele Details und häufige oder umfangreiche Änderungen in erheblichem Maße dazu bei, dass Regelungen – wie solche zu Verrechnungspreisen – als komplex beurteilt werden. Andererseits erweisen sich auch inkonsistente Entscheidungen im Rahmen von Betriebsprüfungen und mangelhafte Gesetzesentwürfe als wesentliche Komplexitätstreiber. Statt einer permanenten Ausweitung von Regulierung sollte künftig der Abbau der im Beitrag identifizierten Probleme gezielt in den Fokus von Wissenschaft, Politik und Praxis rücken.
Keywords: Steuersystem; Komplexität; Steuergesetz; Steuerliche Rahmenbedingungen; BEPS

Funktionsintegration additiv gefertigter Dämpfungsstrukturen bei Biegeschwingungen - Künneke, Thomas; Zimmer, Detmar
Schwingungen und Vibrationen sind in Technik und Alltag häufig anzutreffen. Meist sind sie unerwünscht und müssen durch Dämpfung reduziert werden. Hierzu werden aktuell häufig zusätzlich zu montierende Dämpfungselemente eingesetzt. Diese sind durch zusätzlichen Montageaufwand und erhöhte Kosten gekennzeichnet. Durch die zusätzliche Masse wird Leichtbauansätzen widersprochen. Additive Fertigungsverfahren bieten große Freiheiten in der Bauteilgestaltung. Dies ermöglicht ein hohes Maß an Funktionsintegration. So ergeben sich auch im Bereich der Schwingungsdämpfung Möglichkeiten zur gezielten Integration von Dämpfungsfunktionen durch die Eigenschaften der additiven Fertigungsverfahren. Mittels der pulverbasierten Verfahren kann disperses Stützmaterial innerhalb von Hohlräumen in der Struktur belassen werden. Dieses Pulvermaterial kann als Partikeldämpfer fungieren. Durch die Freiheiten in der Bauteilgestalt kann die Dämpfungswirkung über die geometrischen Merkmale der Hohlräume gezielt eingestellt werden. Im Rahmen dieses Beitrags werden speziell Untersuchungen zur Dämpfungswirkung additiv gefertigter Bauteile bei freien Biegeschwingungen betrachtet. Die praxisnahe Umsetzung zur Funktionsintegration von Dämpfungsstrukturen erfolgt am Beispiel der Ankerscheibe einer Federkraftbremse. Hier kann durch die additive Fertigung verbunden mit der Funktionsintegration von Partikeldämpfern eine Reduzierung der Schallabstrahlung für den Schaltvorgang der Bremse erreicht werden.

Entwicklung und additive Herstellung einer Leichtbau-Rotorwelle für eine permanentmagneterregte Synchronmaschine - Lammers, Stefan; Quattrone, Francesco; Mrozek, Rafael; Zimmer, Detmar; Schmid, Hans-Joachim; Ponick, Bernd; Hoffmann, Michael (Proceedings of the 14th Rapid.Tech Conference)
Additive Fertigungsverfahren (engl.: Additive Manufacturing, kurz: AM) ermöglichen die werkzeuglose Herstellung von Komponenten und kompletten Baugruppen direkt aus dem 3D-CAD-Modell. Insbesondere additiv hergestellte Leichtbaukonstruktionen weisen ein hohes Potential für den Elektromaschinenbau auf. In diesem Paper werden erste Ansätze zur additiven Fertigung einer Rotorwelle für eine permanentmagneterregte Synchronmaschine (PMSM) aufgezeigt. Die Verbesserung einer ausgeprägten Leichtbaukonstruktion der Rotorwelle sowie die Charakterisierung des additiv verarbeiteten Werkstoffs werden aufgeführt. Hierzu wurden Prüfkörper aus dem Werkstoffs H13 (1.2344) hergestellt. Des Weiteren wurden Prüfkörper additiv gefertigter Gitterstrukturen entwickelt und untersucht. Zur Werkstoffcharakterisierung wurden sowohl mechanische Eigenschaften ermittelt, wie die Streckgrenze, die Zugfestigkeit und die Härte als auch elektromagnetische Eigenschaften, wie die Koerzitivfeldstärke, die elektrische Leitfähigkeit und die Permeabilität. Die Ergebnisse zeigen, dass die magnetischen Eigenschaften von H13 durch eine angeschlossene Wärmebehandlung deutlich verbessert werden konnten. Im Anschluss an die Werkstoffcharakterisierung wurde ein innovatives Leichtbau-Rotorwellenkonzept mit internen Gitterstrukturen entwickelt. Verglichen mit einem konventionell gefertigten Rotor konnte die Rotormasse um 25% reduziert werden sowie das Massenträgheitsmoment um 23% reduziert werden bei einer Testdrehzahl von 3000 U/min und einem Drehmoment von 71,98 Nm.

Maßtoleranzen für die additive Fertigung: Experimentelle Untersuchungen für das Lasersintern - Lieneke, Tobias; Adam, Guido; Josupeit, Stefan; Delfs, Patrick; Zimmer, Detmar (Proceedings of the 14th Rapid.Tech Conference)

Dimensional Tolerances for Additive Manufacturing: Fused Deposition Modeling - Knoop, Frederick; Lieneke, Tobias (Inside 3D Printing 2017)

Geometrische Toleranzen für additive Fertigungsverfahren - Lieneke, Tobias; Denzer, Vera; Zimmer, Detmar (3. Summer School Toleranzmangement 2017)

Kombination etablierter und additiver Fertigung: Wirtschaftlicher Einsatz des Laser-Strahlschmelzens (LBM) durch die Kombination mit etablierten Fertigungsverfahren in einer Prozesskette - Eschner, Niclas; Kopf, Robin; Lieneke, Tobias; Künneke, Thomas; Berger, Dietrich; Häfner, Benjamin; Lanza, Gisela; Zimmer, Detmar (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Der Serieneinsatz der additiven Fertigung ist maßgeblich durch die hohen Kosten und der geringen Produktivität der Verfahren limitiert. Der hier vorgestellte Ansatz zeigt, wie die Wirtschaftlichkeit des Laser-Strahlschmelzens (LBM) durch die Kombination mit etablierten Fertigungsverfahren erhöht werden kann. Ziel ist es, nur solche Funktionsträger additiv zu fertigen, die einen höheren Kundennutzen bringen. Dazu werden Konstruktionsrichtlinien definiert, Prozessketten erarbeitet und eine Qualitätssicherung mittels Ultraschallüberwachung realisiert.

Frequenzselektiver Schadensindikator für die Diagnose von Wälzlagerschäden im elektrischen Antriebsstrang - Piantsop Mbo'o, Christelle; Lessmeier, Christian; Zimmer, Detmar; Hameyer, Kay (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Mehrmotorenantriebssysteme - Intelligente Betriebsstrategie - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Datenbasierte Zustandsüberwachung von Wälzlagerschäden in elektromechanischen Antriebssystemen - Lessmeier, Christian

2016 Global MNC Tax Complexity Survey - Executive Summary - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Analyzing Corpus Data from Within - Mindt, Ilka (Anglistik. International Journal of English Studies)

What are the Drivers of Tax Complexity for Multinational Corporations? Evidence from 108 Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments—for example, triggered by the BEPS project—give rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this paper, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax practitioners from 108 countries. Our results show that prior complexity drivers of the tax code are still relevant, with details and changes of tax regulations being the two most influential complexity drivers. We also find evidence for new relevant complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the responses of the practitioners, we develop a concept of tax complexity that distinguishes two pillars, tax code and tax framework complexity, and illustrates the various aspects that should be considered when assessing the complexity of a country’s tax system.
Keywords: Complexity Drivers; International Comparison; Survey; Tax Complexity; Tax Practitioners

Cation-Induced Stabilization and Denaturation of DNA Origami Nanostructures in Urea and Guanidinium Chloride - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Small)

Analysis of acid-base interactions at Al 2 O 3 (11-20) interfaces by means of single molecule force spectroscopy - Mosebach, Bastian; Ozkaya, Berkem; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Constitutions and groups - Mauleon, Ana; Roehl, Nils; Vannetelbosch, Vincent (Games and Economic Behavior)

Scanning Kelvin probe blister studies of the delamination of epoxy films on organosilane modified ZnMgAl alloy coated steel - Grothe, R.; Wiesing, M.; Giner, I.; Meinderink, Dennis; Grundmeier, Guido (Materials and Corrosion)

Electropolymerization of acrylic acid on carbon fibers for improved epoxy/fiber adhesion - Bauer, Andreas; Meinderink, Dennis; Giner, Ignacio; Steger, Helmut; Weitl, Johann; Grundmeier, Guido (Surface and Coatings Technology)

Signaling und Screening - Abbau von Informationsasymmetrie - Golke, Vanessa

Das Reputationssystem als bedeutendes Instrument digitaler Märkte - Moselage, Laura

Der Preis als Qualitätssignal - Hennawi, Mohammad Ziad

Imprecise Matching of Requirements Specifications for Software~Services using Fuzzy Logic - Platenius, Marie Christin; Schäfer, Wilhelm; Shaker, Ammar; Hüllermeier, Eyke; Becker, Matthias (Transactions on Software Engineering)

Ansatz für den Weg in die Plattformökonomie – Das Geschäftsmodell-Technologie-Portfolio - Plass, Christoph; Gausemeier, Jürgen; Drewel, Marvin (Vorausschau und Technologieplanung, Symposium für Vorausschau und Technologieplanung, Band 374)

Identifikation von Potentialen für Augmented-Reality-basierte Produkt-Service-Systeme - Röltgen, Daniel; Wortmann, Fabio; Anacker, Harald; Dumitrescu, Roman (13. Symposium für Vorausschau und Technologieplanung, Band 374 , Berlin , 23. - 24. Nov. 2017)

Modellbasierte Entscheidungsunterstützung in der Produktgenerationenplanung - Albers, Alexander; Kühn, Arno; Dumitrescu, Roman (Proceedings of: Tag des Systems Engineering (TdSE), 8. - 10. Nov. 2017)

Lifshitz analysis of dispersion forces based on quantitative reflection electron energy loss spectroscopy - Wiesing, M.; Grundmeier, Guido (Journal of Colloid and Interface Science)

Corrosive delamination processes of CFRP-aluminum alloy hybrid components - Bauer, A.; Grundmeier, Guido; Steger, H.; Weitl, J. (Materials and Corrosion)

Deformation behavior of nanocrystalline titania particles accessed by complementary in situ electron microscopy techniques - Herre, Patrick; Romeis, Stefan; Mačković, Mirza; Przybilla, Thomas; Paul, Jonas; Schwenger, Jan; Torun, Boray; Grundmeier, Guido; Spiecker, Erdmann; Peukert, Wolfgang (Journal of the American Ceramic Society)

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, M.; Peters, K.; Taube, A.; Keller, A.; Hoyer, K.-P.; Niendorf, T.; Grundmeier, Guido (Materials and Corrosion)

Nanostructured Fe2O3 Processing via Water-Assisted ALD and Low-Temperature CVD from a Versatile Iron Ketoiminate Precursor - Peeters, Daniel; Sadlo, Alexander; Lowjaga, Katarina; Mendoza Reyes, Oliver; Wang, Lidong; Mai, Lukas; Gebhard, Maximilian; Rogalla, Detlef; Becker, Hans-Werner; Giner, Ignacio; Grundmeier, Guido; Mitoraj, Dariusz; et al. (Advanced Materials Interfaces)

New amidinate complexes of indium(iii): promising CVD precursors for transparent and conductive In2O3 thin films - Gebhard, M.; Hellwig, M.; Kroll, A.; Rogalla, D.; Winter, M.; Mallick, B.; Ludwig, A.; Wiesing, M.; Wieck, A. D.; Grundmeier, Guido; Devi, A. (Dalton Transactions)
Heteroleptic and homoleptic In(iii)-amidinate complexes as promising CVD precursors for In2O3 thin films.

Influence of organic surface chemistry on the nucleation of plasma deposited SiOxfilms - Hoppe, Christian; Mitschker, F; Giner, I; de los Arcos, T; Awakowicz, P; Grundmeier, Guido (Journal of Physics D: Applied Physics)

Optionen des Maschinenbaus in der Plattformökonomie von morgen - Drewel, Marvin; Frank, Maximilian; Gausemeier, Jürgen (Vorausschau und Technologieplanung, Symposium für Vorausschau und Technologieplanung, Band 374)
Kaum ein Gebiet weist im Zuge der Digitalisierung so viel Disruptionspotential auf, wie digitale Plattformen. Nachdem es im B2C-Bereich mit Plattformen wie Amazon und Airbnb schon zu gravierenden Veränderungen in der Wettbewerbsarena kommt, steht der B2B-Bereich an der Schwelle zur so genannten Plattformökonomie. Im Maschinenbau versuchen Vorreiter wie Claas und Trumpf mit eigenen Plattformen das Heft des Handelns in die Hand zu bekommen. Das ist aber für kleine und mittlere Unternehmen kaum eine Erfolg versprechende Option, da es zu einem Shake Out unter den Plattformanbietern kommen wird und nur wenige Große überleben werden. Für KMU zeichnet sich schon jetzt die Bedrohung ab, dass sie den direkten Kundenkontakt verlieren und zu austauschbaren Ausführern werden. Im Grunde fehlt insbesondere den mittelständisch geprägten Unternehmen eine Strategie zur vorteilhaften Positionierung in der künftigen Plattformökonomie. Wir zeigen, wie sich mit Hilfe der Szenario-Technik strategische Optionen für den Maschinenbau mit einem Zeithorizont 2030 ableiten lassen. Das beruht auf der Antizipation der künftigen Rahmenbedingungen der Plattformökonomie sowie auf alternativen Gestaltungsmöglichkeiten der Unternehmen. Aus heutiger Sicht deutet alles darauf hin, dass die Unternehmen mit Rahmenbedingungen zu rechnen haben, die sich unter dem Szenario mit dem Titel „Erfolgreicher Mittelstand mit staatlicher Unterstützung“ charakterisieren lassen. In dieser Situation bietet sich für die hier betrachtete Branche die Gestaltungsoption mit dem Titel „Kooperationen als Schlüssel zum Erfolg“ an. Aus dieser strategischen Stoßrichtung werden Handlungsempfehlungen für die Branche und für einzelne Unternehmen formuliert. Die vorgestellten Ergebnisse basieren auf ausführlichen Interviews mit namhaften Experten des Maschinenbaus und aus dem Bereich Plattformökonomie. Die Arbeit ist als ein methodischer Ansatz zu verstehen, sich mit dem durch die Digitalisierung induszierten Wandel der Wettbewerbsarena des Maschinenbaus fundiert auseinanderzusetzen.

Mechatronic Modularization of Intelligent Technical Systems - Lipsmeier, Andre; Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman (21th International Conference on Engineering and Design (ICED17), 21. - 25. Aug. 2017)

Kundenorientierte Entwicklung von Intelligenten Technischen Systemen im Maschinenbau - Lipsmeier, Andre; Anacker, Harald; Dumitrescu, Roman; Kühn, Arno (Stuttgarter Symposium für Produktentwicklung SSP 2017, Stuttgart, 28. - 29. Jun. 2017)

Integrated technology transfer concept for fostering innovation in SMEs - Fechtelpeter, Christian; Kühn, Arno; Dumitrescu, Roman; Ebbesmeyer, Peter (Proceedings of the 26th International Association for Management of Technology Conference , 14. - 18. Mai 2017, IAMOT)

Erfolgsgarant digitale Plattform – Vorreiter Landwirtschaft - Drewel, Marvin; Gausemeier, Jürgen; Kluge, Andre; Pierenkemper, Christoph (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017, Band 369)

Implementation planning and transfer of technology induced scenarios of digitized work - Fechtelpeter, Christian; Bansmann, Michael; Dumitrescu, Roman; Anacker, Harald (Presentation and proceedings, Technology Transfer Society (T2S) Annual Conference, 2017)

Reifegradmodell für die Planung von Cyber-Physical Systems - Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman (Wissenschafts- und Industrieforum 2017 - Intelligente Technische Systeme, Band 369)

Schichtenmodell für die Entwicklung von Data Science Anwendungen im Maschinen- und Anlagenbau - Reinhart, Felix; Kühn, Arno; Dumitrescu, Roman (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys),)

Integrierte Entwicklung komplexer Systeme mit modellbasierter Systemspezifikation und -simulation - Eine Fallstudie zur Sensorauslegung in der Raumfahrt - Roßmann, Jürgen; Schluse, Michael; Rast, Malte; Hoppen, Martin; Atorf, Linus; Dumitrescu, Roman; Bremer, Christian; Hillebrand, Michael; Stern, Oliver; Schmitter, Peter (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Virtuelle Inbetriebnahme eines Fertigungszentrums - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Tag des System Engineering)

Systematische Inbetriebnahme einer Prüfeinrichtung für Zugversuche - Holtkötter, Jens; Michael, Jan; Henke, Christian (Virtuelle Instrumente in der Praxis 2017)

Modellbasierte Untersuchung der Zuverlässigkeit algorithmisch bestimmter kritischer Stellen in Straßennetzwerken - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Fast hybrid position / force control of a parallel kinematic load simulator for 6-DOF Hardware-in-the-Loop axle tests - Kohlstedt, Andreas; Traphöner, Phillip; Olma, Simon; Jäker, Karl-Peter; Trächtler, Ansgar (2017 IEEE International Conference on Advanced Intelligent Mechatronics (AIM))

Nonlinear Model Predictive Control with Discrete Mechanics and Optimal Control - Xu, Ke; Timmermann, Julia; Trächtler, Ansgar (Proc. Advanced Intelligent Mechatronics (AIM))

Swing-up of the moving double pendulum on a cart with simulation based LQR-Trees - Xu, Ke; Timmermann, Julia; Trächtler, Ansgar (Proc. 20th IFAC World Congress)

Networked Driving Simulation for Future Autonomous and Cooperative Vehicle Systems - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Model-Based Design of Self-Correcting Forming Processes - Krüger, Martin; Borsig, Michael; Damerow, Ulf-Hendrik; Gräler, Manuel; Trächtler, Ansgar (Math for the Digital Factory)

Universelle Entwicklungs- und Prüfumgebung für mechatronische Fahrzeugachsen - Traphöner, Phillip; Olma, Simon; Kohlstedt, Andreas; Jäker, Karl-Peter; Trächtler, Ansgar (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017)

Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) - Gausemeier, Jürgen; Bodden, Eric; Dressler, Falko; Dumitrescu, Roman; Meyer auf der Heide, Friedhelm; Scheytt, Christoph; Trächtler, Ansgar

A Holistic Approach for Virtual Commissioning of Intelligent Systems - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Systems Conference 2017)

Dynamische Prozessplanung im Smart Home auf Basis von Mutliagentensystemen - Michael, Jan; Hellweg, Alina; Henke, Christian; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Kinematics-based force/position control of a hexapod in a HiL axle test rig - Kohlstedt, Andreas; Olma, Simon; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (17. Internationales Stuttgarter Symposium, Band 2)

Modellprädiktive Vorsteuerung für einen kinematisch redundanten hybridkinematischen Mechanismus im Industrieumfeld - Rüting, Arne Thorsten; Block, Eduard; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Adaptive Sigma-Punkte- Filter-Auslegung zur Zustands- und Parameterschätzung an Black-Box- Modellen - Schweers, Christoph

Innovative Suspensions for Caterpillar Vehicles - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Russian Engineering Research)

Methodology for Determining Critical Locations in Road Networks based on Graph Theory - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (IFAC World Congress 2017)

Sliding-Mode-Regler zur Kraft- und Positionsregelung eines Formgedächtnislegierung-Aktors - Pai, Arathi (Regelungstechnisches Kolloquium)

Scientifc Automation: Hochpräzise Analysen direkt in der Steuerung - Papenfort, Josef; Bause, Fabian; Frank, Ursula; Strughold, Sebastian; Trächtler, Ansgar; Bielawny, Dirk; Henke, Christian (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Reliable Multipath Communication Approach for Internet-based Cyber-physical Systems - Elattar, Mohammad; Jasperneite, Jürgen; Trächtler, Ansgar; et, al (26th IEEE International Symposium on Industrial Electronics (ISIE))

Flachheitsbasierte Positionsregelungen für Parallelkinematiken am Beispiel eines hochdynamischen Hexapoden - Knoop, Sarah

Mechanisch - mathematisches Modell eines Kettenfahrzeuges für die Entwicklung innovativer Antriebs- und Federungssysteme (auf russ.) - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Interbranch Scientific and Technical Magazine «Vestnik Mashinostroeniya»)

Rational Decision-Making for the Beneficial Application of Additive Manufacturing - Deppe, G.; Koch, R.; Kaesberg, M. (28th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing is a technology that offers a high potential forindustrial companies.Nevertheless, companies lack experience with this new technology and face the problem to identify processes where a successful and beneficial application can be achieved. They have to be supported in this analysis with a decision support tool which is capable to compare different manufacturing or repair approaches in order to determine the optimal solution for the correspondent use case. This is not always driven solely by costs but can also be critically affected by further influencing factors. This is why the decision support takes into account also time and quality alongside the costs. For a time-critical spare part supply, for example within aerospace sector, they are substantial for taking a decision. The presented decision support features a multi-attribute decision-making approach for selecting the most appropriate process, either Additive Manufacturing, conventional technologies or an external procurement.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Integrating AM into existing companies - selection of existing parts for increase of acceptance - Kruse, A.; Reiher, T.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In many branches in the designengineerdepartment, product designs are just variations of existing parts. To bring the additive manufacturing technology closer to the Designer, it is necessary to show them which of their existing, conventionally manufactured parts can be produced with this technology. Apartselection methodology supportsdesigners in the decision whether a part is suitable for additive manufacturingor not. Due to the potential of the technology, which was especially seen in the aerospace industries, many criteria of the methodology were initially adapted for this industry. Furthermore the methodology is based on a quantified weighting system, which comes to a certain subjectivity. For future use, a development towards a less subjective methodology should be accomplished. Through a more detailed adaption for individual industries and a simplification of the input mode, the objectivity of the criteria can be increased. Likewise, the input time can be reduced by simplifying the questioning. A more efficient part selection will be achieved by a better weighting system.In the BMBF project “OptiAMix” this methodology is supposed to be further developed for highly different branches. By a better weighting system, the part selection will be more efficient. Therefore,the willingness for the use of the improved selection andfor the additive manufacturing technology will be increased.

Design for protection: Systematic approach to prevent product piracy during product development using AM - Jahnke, U.; Koch, R.; Oppermann, A. T. (28th Annual International Solid Freeform Fabrication Symposium)
Although infringements of intellectual properties in terms of product piracy are growing for years and threaten investments in research and development most companies still rely on legal measures like property rights. A more preventive effect to protect against counterfeits can be achieved using technical measures complicating reverse engineering, improving traceability and assuring data protection. Additive Manufacturing can contribute a lot to the effectivity and efficiency of those technical measures but presently they are often unconsidered during product development. To support decision makers and designers through all the steps of a product development process an integrated systematic approach has been developed. Protective measures using AM are allocated to specific process steps and responsible persons in charge so that the result is a guideline for “design for protection”. The main idea is to help developing piracy-robust products for that the return of investment is not threatened by counterfeits and its economical impacts.

Ramp-Up-Management in Additive Manufacturing – Technology Integration in existing Business Processes - Büsching, J.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In conventional manufacturing, ramp-up-management describes the planning and organization of the period between finished product development and the achievement of full production capacity for defined products. This classification has to be adapted and restructured by means of product independent and tool-free production in additive manufacturing. Therefore ramp-up-management already starts with decisions on the extentof the use of additive manufacturing, includes the building of technology-know-how as well as the technology integration into processes and infrastructure of the company and ends with the attainment of a sufficient process reliability for the AM-machine. This paper focuses on technology integration in processes and infrastructure, which is part of the German research project OptiAMix. In this project, new systems for process state analysis adapted to additive manufacturing and methods for the optimal integration of additive manufacturing are developed. Furthermore ways of using the synergies of existing infrastructures and new innovative production technologies are determined.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Hybrid Manufacturing with Additive Manufacturing - Deppe, G.; Lindemann, C. (CECIMO Magazine)
Additive Manufacturing provides an outstanding technological and economic potential for a wide range of industries. Particularly in the field of small series production with many product variants, the technology offers decisive advantages, such as reducing component weight, functional integration, complex parts or individualization. Today potential users struggle with the integration of this technology in their businesses. The production costs of this technology often seem too high compared to traditionally manufactured parts and many users seem disappointed with the performance of the technology. The reasons for that are manifold, but often Additive Manufacturing is considered only as an isolated technology.

Holistic approach for industrializing AM technology - from part selection to test and verification - Reiher, T.; Lindemann, C.; Jahnke, U.; Deppe, G.; Koch, R. (Progress in Additive Manufacturing)
Even in times where additive manufacturing has a peak in media and industry interest, only few companies have already implemented this technology. Many companies struggle with the use of AM even if they have already identified the benefits of this technology for their business. Additional knowledge along the whole product development chain is necessary to succeed in implementing this technology. As all other production technologies, AM has certain strength and weaknesses which affect the suitable part candidates. Redesign or manufacturing approaches of unsuited part candidates are no very likely to be successful. In general, aspects like design rules need to be known along the product development process in order to achieve technology-based benefits during production and post-processing resulting in economic success. This paper will present a holistic approach which will assist the designer during product development and manufacturing based on an example part from the space industry. Then methodology starts with an appropriate part selection as a key parameter for the product development process. Based on the promising part candidates, deductions for the further product development process will be described. This includes approaches for functional integration as well as a methodology for the compilation of part requirements. Those are utilized for a black box methodology, ensuring a time-efficient redesign based on FEA optimization and design rules for additive manufacturing. Best practices for integrating (or in the best case avoiding) traditional technologies are discussed. Based on this, the development of industrialization and test and verification plans for production are shown. This includes the marking of parts for traceability during the whole product lifecycle for quality reasons as well as for product protection. Furthermore, production and production planning are discussed. This is followed by post-processing and testing procedures of the part. The paper will close with a detailed economic view on the topic and some deductions regarding the changes in the supply chain. The methodology itself is discussed and explained on a real sample metal part. The general methodology is discussed on the basis of the space industry but is subject to be adapted to other industries.

CLIL theory and empirical reality – Two sides of the same coin? - Rumlich, Dominik (Journal of Immersion and Content-Based Language Education)

The rich environment of CLIL classes as an ideal setting for collaborative learning - Rumlich, Dominik; Ahlers, Sabine (Collaborative learning and new media)

Markov state models from short non-equilibrium simulations—Analysis and correction of estimation bias - Nüske, Feliks; Wu, Hao; Prinz, Jan-Hendrik; Wehmeyer, Christoph; Clementi, Cecilia; Noé, Frank (The Journal of Chemical Physics)

Variational Koopman models: Slow collective variables and molecular kinetics from short off-equilibrium simulations - Wu, Hao; Nüske, Feliks; Paul, Fabian; Klus, Stefan; Koltai, Péter; Noé, Frank (The Journal of Chemical Physics)

Reproduzierbarkeit der Maßhaltigkeit im Fused Deposition Modeling - Knoop, F.; Lieneke, Tobias; Schöppner, Volker (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
Fused Deposition Modeling (FDM) is used for prototypes, single-partproduction and small batch productions of thermoplastic components. This manufacturing technique has the huge benefit that no forming tool is needed. The knowledge about dimensional deviations which occur in the FDM process is necessary for calculating fits and for determining tolerances. A major challenge is the reproducibility of the dimensional accuracy of FDM parts and the reproducibility between different FDM machines. There are many influential factors on the dimensional accuracy in the FDM process for example geometric, material-specific or process-specific factors, which are considered in this paper. The influence of the part position on the build platform of a Stratasys Fortus 400mc is analyzed in terms of the achievable dimensional accuracy. For this purpose, the temperature distribution in the actively heated build chamber is investigated and possible correlations to the dimensional accuracy are identified. The reproducibility of one machine is examined by a multiple production of the test specimens. In addition, a comparison with three other FDM machines from Stratasys is made. Afterwards, the long-term reproducibility of the dimensional accuracy is verified to consider how environmental influences such as maintenance or modification of machine components affect the dimensional accuracy of the FDM process.

Considering machine- and process-specific influences to create custom-built specimens for the Fused Deposition Modeling process - Schumacher, C.; Schöppner, Volker; Guntermann, J. (28th Annual International Solid Freeform Fabrication Symposium)
Compared to conventional polymer processing technologies the material selection in the Fused Deposition Modelling (FDM) process is restricted. To expand the range of materials the requirements for the material properties and the semi-finished products (filaments) must be clarified. For this, a machine- and process-independent rating of the processability is necessary. The established standards for the tensile strength test apply to specimens with nearly isotropic mechanical properties. The FDM process generates anisotropic parts. The properties are mainly influenced by the machine quality and the data processing. It is not possible to test a material for FDM independently of the machine and the data processing. In this paper, machine and process specific influences are investigated. Considering these influences, a custom-built specimen is created to test the tensile strength of the welding seams for polyamide 6. This procedure allows a machine- and process-independent rating of the processability in terms of tensile strength for different materials.

Geometrical Accuracy of Holes and Cylinders Manufactured with Fused Deposition Modeling - Knoop, F.; Schöppner, Volker (28th Annual International Solid Freeform Fabrication Symposium)
A widely used Additive Manufacturing (AM) technology is Fused Deposition Modeling (FDM) to create prototypes and end-use parts with close-to-production thermoplastics. For their use as a final product, it is necessary that additively manufactured parts strictly adhere to the geometrical requirements of the technical drawing. In this paper, the holes and cylinders of the cylindrical elements are investigated in terms of achievable geometrical accuracy. For this purpose, different test specimens that allow a measurement of inner and outer diameters from 3 to 80 mm were designed. All specimens were measured with a coordinate measuring machine (CMM) to evaluate deviations from the nominal dimension and form deviations. The measuring method includes a scanning of the surface to record the course of dimensional deviations over the diameter. Thus, it was possible to visualize how deviations on cylindrical elements manufactured in FDM occur. In order to counteract these deviations and to improve the dimensional accuracy, different shrink factors and filling patterns were investigated. Consequently, an improvement of the dimensional accuracy was achieved.

Beurteilung der Schweißnahtfestigkeiten verschiedener Kunststoffe im FDM-Prozess - Schöppner, Volker; Schumacher, C.; Guntermann, J. (Jahresmagazin Kunststofftechnik)
Um die Materialauswahl für den FDM-Prozess zu steigern, sollten die durch den FDM-Prozess an das Material gestellten Anforderungen bekannt sein. Dazu ist eine von der Maschine und der individuellen Datenaufbereitung möglichst unabhängige Bewertung der FDM-Verarbeitungseignung wünschenswert. In diesem Artikel werden eine Prüfmethode und ein dazu entwickelter Probekörper vorgestellt, mit dem die Schweißnahtfestigkeit verschiedener Polyamid 6 Typen im FDM-Prozess ermittelt und verglichen wird.